The Right Price of Food: Reflections on the Political Economy of Policy Analysis and Communication - Johan F.M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
Only a few years ago the widely shared view was that low food prices were a curse to developing countries and the poor. The dramatic increase of food prices in 2006-2008 appears to have fundamentally altered this view. The vast majority of analyses and reports in 2008 and 2009 state that high food prices have a devastating effect on developing countries and the world's poor. This reversal of opinion raises questions about the old and the new arguments and about the proposed remedies. It also raises questions about the causes of this dramatic turnaround in analysis and policy conclusions. In this paper I document these changes in perspective and I discuss potential implications and offer hypotheses on the cause of the change in views.
Keywords: J11; J15; Y80; 330; Nahrungsmittelpreis; Nahrungsmittelpreispolitik; Entwicklungsländer